Judicial Reasoning in Child Guardianship: Gender Justice and Maqāṣid Al-Sharī'ah in Indonesian Religious Courts - Martius Martius; Musyaffa Amin Ash Shabah; Azhar Muhamad Akbar; E-bat Che-umong; Restia Gustiana (Universitas Muhammadiyah Bandung, 2025)
Child guardianship (ḥaḍānah) in Islamic family law represents a critical mechanism for child protection during family dissolution, yet existing scholarship remains predominantly normative and fragmented, lacking longitudinal socio-legal analysis of judicial reasoning that integrates child protection and gender justice within Islamic legal frameworks. This study aims to analyze the transformation of child guardianship adjudication in Indonesian Religious Courts (Pengadilan Agama) during 2020–2025, focusing on judicial reasoning patterns, child welfare orientations, and the positioning of women's rights. Employing a normative-empirical (socio-legal) approach, this study analyzed 120 guardianship decisions retrieved from the Supreme Court Verdict Directory through qualitative content analysis and systematic coding, integrating three analytical frameworks: the best interest of the child, maqāṣid al-sharī'ah, and gender justice theory. The findings reveal a significant shift from textualist-normative reasoning toward discretionary, welfare-oriented adjudication, with judges increasingly prioritizing emotional stability, caregiving continuity, and socioeconomic conditions. A pronounced maternal preference pattern was identified, reflecting caregiving realities while simultaneously indicating latent gender bias. Women's rights were found to be implicitly integrated yet structurally subordinated within the best interest framework rather than recognized as autonomous legal principles. The COVID-19 pandemic additionally functioned as a structural catalyst accelerating guardianship litigation. This study contributes a longitudinal socio-legal framework that bridges maqāṣid al-sharī'ah with contemporary human rights discourse, while critically exposing the risks of unchecked judicial subjectivity. These findings underscore the urgent need for verdict standardization, explicit gender justice integration, and systematic reform of Islamic family law in Indonesia.